Structural and Oxidation State Alternatives in Platinum and Palladium Complexes of a Redox‐Active Amidinato Ligand - Ehret, Fabian; Filippou, Vasileios; Blickle, Svenja; Bubrin, Martina; Záliš, Stanislav; Kaim, Wolfgang (Chemistry : a European journal, 2021)
Reaction of [Pt(DMSO)2Cl2] or [Pd(MeCN)2Cl2] with the electron‐rich LH=N,N’‐bis(4‐dimethylaminophenyl)ethanimidamide yielded mononuclear [PtL2] (1) but dinuclear [Pd2L4] (2), a paddle‐wheel complex. The neutral compounds were characterized through experiments (crystal structures, electrochemistry, UV‐vis‐NIR spectroscopy, magnetic resonance) and TD‐DFT calculations as metal(II) species with noninnocent ligands L−. The reversibly accessible cations [PtL2]+ and [Pd2L4]+ were also studied, the latter as [Pd2L4][B{3,5‐(CF3)2C6H3}4] single crystals. Experimental and computational investigations were directed at the elucidation of the electronic structures, establishing the correct oxidation states within the alternatives [PtII(L−)2] or [Pt.(L )2], [PtII(L0.5−)2]+ or [PtIII(L−)2]+, [(PdII)2(μ‐L−)4] or [(Pd1.5)2(μ‐L0.75−)4], and [(Pd2.5)2(μ‐L−)4]+ or [(PdII)2(μ‐L0.75−)4]+. In each case, the first alternative was shown to be most appropriate. Remarkable results include the preference of platinum for mononuclear planar [PtL2] with an N‐Pt‐N bite angle of 62.8(2)° in contrast to [Pd2L4], and the dimetal (Pd24+→Pd25+) instead of ligand (L−→L ) oxidation of the dinuclear palladium compound. Qualitatively different structures and electron transfer behavior have been established for platinum and palladium complexes [PtL2]0/+ and [Pd2L4]0/+ with a redox‐active amidinato ligand L−/L..